Angiotensin II induces differential insulin action in rat skeletal muscle. Issue 3 (March 2017) - Surapongchai, Juthamard; Prasannarong, Mujalin; Bupha-Intr, Tepmanas; Saengsirisuwan, Vitoon
Abstract : Angiotensin II (ANGII) is reportedly involved in the development of skeletal muscle insulin resistance. The present investigation evaluated the effects of two ANGII doses on the phenotypic characteristics of insulin resistance syndrome and insulin action and signaling in rat skeletal muscle. Male Sprague–Dawley rats were infused with either saline (SHAM) or ANGII at a commonly used pressor dose (100 ng/kg/min; ANGII-100) or a higher pressor dose (500 ng/kg/min; ANGII-500) via osmotic minipumps for 14 days. We demonstrated that ANGII-100-infused rats exhibited the phenotypic features of non-obese insulin resistance syndrome, including hypertension, impaired glucose tolerance and insulin resistance of glucose uptake in the soleus muscle, whereas ANGII-500-treated rats exhibited diabetes-like symptoms, such as post-prandial hyperglycemia, impaired insulin secretion and hypertriglyceridemia. At the cellular level, insulin-stimulated glucose uptake in the soleus muscle of the ANGII-100 group was 33% lower ( P  < 0.05) than that in the SHAM group and was associated with increased insulin-stimulated IRS-1 Ser 307 and decreased Akt Ser 473 and AS160 Thr 642 phosphorylation and GLUT-4 expression. However, ANGII-500 infusion did not induce skeletal muscle insulin resistance or impair insulin signaling elements as initially anticipated. Moreover, we found that insulin-stimulated glucose uptake in the ANGII-500 group was accompanied by the enhanced expression of ACE2 and MasR proteins, which are the key elements in the non-classical pathway of the renin–angiotensin system. Collectively, this study demonstrates for the first time that chronic infusion with these two pressor doses of ANGII induced differential metabolic responses at both the systemic and skeletal muscle levels.